Integrating transcriptome and proteome profiles to compare carcass and meat quality traits between Songliao and Songlei black pigs - Zhang, Yunpeng; Zhang, Qi; Kumar, Suthar Teerath; Xu, Jing; Xie, Yupeng; Wang, Zhihao; Sun, Wu-Sheng; Pan, Li; Zhao, Yuan; Zhang, Shu-Min (Frontiers in Nutrition, 2026)
With the ongoing upgrade in consumption patterns, the pork market is shifting from a focus on quantity to an emphasis on quality, demanding higher intramuscular fat content alongside maintained growth rates. Crossbreeding between the Chinese lean-type Songliao black pig and the high-quality local breed Leixiang pig allows rapid integration of parental superior traits, resulting in hybrid vigor that effectively improves pork quality, growth performance, and economic benefits. We conducted transcriptomic and 4D microDIA proteomic sequencing analyses on the longissimus dorsi muscle tissue from hybrid offspring of purebred Songliao black pigs and Songliao × Leixiang black pigs. Extensive phenotypic analyses were performed on Songliao black pigs and Songlei black pigs using multiple trait indicators. Six pigs were selected and categorized into relatively high and low intramuscular fat groups. Integrated analysis of transcriptomic and proteomic data identified candidate genes within significantly annotated lipid-related pathways via KEGG, including ACSL1, ACSL6, SREBF1, PLIN2, CEPT1, CPT1B, CPT1C, and ACSF3. Among these, CPT1B was significantly associated with fatty acid metabolism pathways. By analyzing all significantly differential genes and proteins, six candidate genes were identified as key determinants of genetic variation in lipid deposition: UCP3, CPT1B, LSMEM1, NEXN, PPP1R14C, and LOC100624149. This preliminary exploratory multi-omics study provides a valuable resource for probing intramuscular fat deposition, aiming to support pork-trait improvement in breeding and to establish a fresh theoretical basis for clarifying the molecular mechanisms of meat-quality heterosis in Songlei black pigs.